Perancangan Fasilitas Pendidikan Anak Usia Dini Desa Gunung Sari Kecamatan Mauk Kabupaten Tangerang - Susinety Prakoso; Felia Srinaga; Julia Dewi; Dicky Tanumihardja; Santoni Santoni (Jurnal Sinergitas PKM & CSR, 2016)
AbstractThis paper demonstrates the design process of Early Childhood Education Center (ECDC) in Gunung Sari Village at Mauk, Tangerang. This project is a collaborative community service between the Architecture Department at Universitas Pelita Harapan and Habitat for Humanity Indonesia. This paper highlights the design process of ECDC involving pre-school’s children through mosaic approach developed by Clark and Moss (2011). The aim of this approach is to contribute to the design of ECDC that is meaningful and responsive to young children’s needs. Mosaic approach is based on a participatory method that recognize young children’s competencies and responsive to the ‘voice’ of the young children (aged 3-6). Three stages of mosaic approach have been applied: 1) gathering children’s and adult’s perspectives; 2) discussing (reviewing) the material; 3) discussing on areas of continuity and change. Observation, child-conferencing and mapping are three different techniques of mosaic approach that have been applied in this study. The end process of the design of ECDC is in the form of technical drawings, images and model that will be used by Habitat for Humanity Indonesia in the construction process. This paper also reflects on key lessons learned in working with young children through participation process and mosaic approach.  Keywords:  design process, early childhood education center, participation, mosaic approach.AbstrakTulisan ini bertujuan untuk berbagi pengalaman proses perancangan bangunan Pendidikan Anak Usia Dini (PAUD) di Desa Gunung Sari Kecamatan Mauk, Tangerang. Kegiatan ini merupakan kerjasama program studi Arsitektur Universitas Pelita Harapan dengan Habitat for Humanity Indonesia, sebagai bagian dari kegiatan Pengabdian kepada Masyarakat (PkM). Proses perancangan bangunan PAUD menggunakan pendekatan partisipasi dengan teknik mosaic approach (Clark and Moss, 2011), dengan tujuan untuk menghasilkan rancangan yang peka terhadap kebutuhan anak serta bermakna bagi anak. Mosaic approach merupakan pendekatan penelitian yang digunakan untuk mendengar ‘suara’ anak dan mengakui kompetensi anak, terutama anak usia pra-sekolah (3-6 tahun). Tiga tahapan mosaic approach diterapkan dalam proses perancangan meliputi: 1) mengumpulkan pandangan anak dan orang dewasa; 2) membahas material yang terkumpul; 3) memutuskan apa yang perlu diteruskan dan diubah. Prinsip multi method mosaic approach yang dilaksanakan adalah observasi, child conferencing dan mapping. Hasil dari keseluruhan proses perancangan bangunan PAUD adalah rancangan final PAUD dalam bentuk gambar kerja, gambar presentasi serta maket bangunan yang digunakan oleh pihak Habitat for Humanity Indonesia untuk pelaksanaan pembangunan fisik di lapangan. Tulisan ini fokus pada pendekatan partisipasi dengan teknik mosaic approach yang digunakan dalam melaksanakan proses perancangan bangunan PAUD, serta mendeskripsikan evaluasi keberhasilan pendekatan partisipasi dan teknik mosaic approach.Kata kunci: proses perancangan, sekolah, partisipasi, mosaic approach, anak